A SURVEY AND COMPARISON ON USER AUTHENTICATION METHODS - Prof. Jyoti I. Nandalwar; Prof. Viteshkumar Gaikwad; Prof. Shripad Kulkarni (International Journal of Innovations in Engineering Research and Technology, 2021)
Today security concerns are on the rise in all area such as banks, government organizations, business organizations, educational institute etc. The number of frauds and abuses are literally exploding with the increase use of internet in every field. Among all frauds and abuses, the most serious is the theft of identity which causes grave damage to the victim. The protection of digital identities is getting more and more crucial. The use of password for authentication is no longer sufficient and stronger authentication schemesare necessary factor in keeping security of your system. Authentication scheme is a fundamental and important subject for network security, because it is usually used to protect sensitive and important information to restrict the access of precious resources for legal users only. Several authentication strategies have been proposed, soma of which are very difficult to use and others might not meet company’s security concern. So it has become crucial to have in depth knowledge of all authentication schemes so that user can choose best among them as per user’s requirement. In this paper we have first studied different types of accounts user can have based on their sensitivity, then we have studied what is authentication,